THE RELATIONSHIP BETWEEN VITAMIN D3 LEVELS AND HYPOTHYROIDISM - Mustafa, Dilshad Hamad; Mohammed, Ribwar Arsalan; Asaad, Aveen Muhsin; Hawezy, Dawan Jamal (Journal of Sulaimani Medical College, 2022)
Background It has been well observed that vitamin D deficiency may increase the prevalence of hypothyroidism. However, there is little information on the relationship between vitamin D levels and thyroid diseases amongst the Kurdish population. Objectives To find an association between thyroid function parameters and levels of Vit. D among two different groups. Patients and Methods A case-control study was employed; two groups participated in the study, the first group was healthy individuals, and the other group was those with hypothyroidism. Results The results of 90 persons were collected in the recent study. The mean age was 42.76 ± 9.47. The majority of the participants were women (52.2%). Vitamin D levels were deficient in most participants (50%), which means lower than 20.1 ng/ ml. Only about 37% of the participants had an average level of Vit. D. Conclusion Deficiency in Vitamin D3 is significantly associated with all thyroid function parameters.
Keywords: Relationship; Vitamin D3; and Hypothyroidism